Recurrent Larnygeal Nerve Injury in Endoscopic Hemithyroidectomy - Hazrat Bilal, Shoaib Malik, Zahid Mehmood, Hurtamina Khan, Maham Imran, Mariam Imran, Nazia Haider, Ghansham, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find the frequency of recurrent laryngeal nerve damage in endoscopic thyroidectomy. Study design: Cross sectional descriptive study Place & Duration of study: Ward 25, Jinnah Postgraduate Medical Centre, Karachi, Pakistan from January 2018 to January 2021. Methodology: Eighty patients of solitary thyroid nodules who fulfill inclusion criteria were divided alternatively into endoscopic and open hemi thyroidectomy groups. Patients were assessed for recurrent laryngeal nerve injury in the evening and after 24 hours of surgery by quality of voice. Those patients whose voice is normal discharge on 2nd day while others follow fortnightly until 3 months. Results: There was no recurrent laryngeal nerve injury encountered in group A while in group B 4 (10%) transient recurrent laryngeal nerve injuries were encountered. All injuries were recovered within 3 months post operatively. Out of 4 recurrent laryngeal nerve injuries 3 (75%) on left side (left hemi thyroidectomy) while 1 (25%) on right hemithyroidectomy.2 (50%) recurrent laryngeal nerve injuries in patients when surgery time was approximately 3 hours. Conclusion: Endoscopic thyroidectomy is safe, feasible and emerging minimal invasive technique to remove the thyroid gland without visible scar. Keywords: Recurrent laryngeal nerve, Endoscopic thyroidectomy, Solitary thyroid nodule